ARTERIAL HYPERTENSION MANAGEMENT IN PATIENTS AGED OLDER THAN 80 YEARS AND PATIENTS WITH THE SENILE ASTHENIA - O. N. Tkacheva; N. K. Runikhina; Yu. V. Kotovskaya; N. V. Sharashkina; V. S. Ostapenko (Кардиоваскулярная терапия и профилактика, 2017)
A position agreement of the experts of Russian association of gerontologists and geriatricians, Gerontological society of Russian Academy of Sciences,  Russian medical society for arterial hypertensionTask Force Members: Tkacheva O. N. (Chairperson), Runikhina N. K., Kotovskaya Yu. V., Sharashkina N. V., Ostapenko V. S.Expert Committee: Anisimov V. N., Arkhipov M. V., Baranova E. I., Boytsov S. A., Bolotnova T. V., Villevalde S. V., Galyavich A. S., Grinshtein Yu. I., Drapkina O. M., Duplyakov D. V., Zhernakova Yu. V., Zakharova N. O., Ilnitsky A. N., Karaeva E. V., Karpov Yu. A., Kisliak O. A., Kobalava Zh. D., Koziolova N. A., Konradi A. O., Martynov A. I., Medvedeva I. V., Moiseev V. S., Nedogoda S. V., Oganov R. G., Orlova Ya. A., Ostroumova O. D., Oschepkova E. V., Podzolkov V. I., Proschaev K. I., Skibitsky V. V., Fomin I. V., Frolova E. V., Khavinson V. Kh., Chazova I. E., Chesnikova A. I., Chukaeva I. I., Shabalin V. N.